The association of oral function with dietary intake and nutritional status among older adults: Latest evidence from epidemiological studies - Masanori Iwasaki; Hirohiko Hirano; Yuki Ohara; Keiko Motokawa (Elsevier, 2021)
Inadequate and poor quality of diet and malnutrition are common and associated with adverse health outcomes, including morbidity and mortality, among older persons. This review aimed to establish the latest evidence from studies investigating the association between oral function and nutrition among older adults.An electronic search of MEDLINE using PubMed for literature published in English between March 2018 and March 2021 was conducted, and 27 papers were identified. The selected studies comprised 23 observational studies (17 cross-sectional and 6 longitudinal studies) and 4 interventional studies. Most of the observational studies demonstrated the following associations in older adults: older adults with poor oral function are likely to have poorer dietary intake and poorer nutritional status, and malnourished older adults are likely to have poorer oral function. The results of the intervention studies demonstrated that the combination of prosthodontic treatment and dietary counseling is more effective for improving dietary intake and nutritional status in older persons with tooth loss than the prosthodontic treatment alone.Our review confirmed that a relationship exists between oral function and nutrition and revealed the need for additional high-quality studies investigating comprehensive oral function, rather than a single aspect of oral function, with regard to nutritional status.